The mirroring of intercultural and hybridity experiences: A study of African immigrant social entrepreneurs - Mafico, Nkosana; Krzeminska, Anna; Härtel, Charmine; Keller, Josh (Journal of Business Venturing, 2021)
Paradox theory is attracting increasing interest from entrepreneurship scholars seeking to understand how entrepreneurs who operate hybrid organizations such as prosocial ventures can effectively address grand challenges. The organizational paradox literature suggests that differences in actors' approach to paradoxes can occur through the acquisition of different reasoning styles through exposure to different national cultures and cultural resources. We complement the paradox research stream on culture as a resource with the alternative perspective of culture as an experience, which we argue offers additional insight into hybridity within a global context because intercultural experiences are intrinsically paradoxical. Our 18 case studies of immigrant entrepreneurs from the African diaspora operating their prosocial ventures in Western contexts finds that the ways that immigrant entrepreneurs approach tensions in their prosocial ventures mirrors the nature of their intercultural experience. We also find that approaches to paradox vary based on structural barriers such as social exclusion that entrepreneurs faced in their formative years. Overall, our study contributes to research on culture in paradox theory and the prosocial venturing literature by elucidating how entrepreneurs' intercultural experience and the global macro-level systems in which it is embedded inform the degree and configurations of hybridity in prosocial ventures.